The Effect of Multidimensional Sexual Education-Counseling on Sexual Knowledge and Attitudes of Couples Preparing for Marriage - Soghra Khani; Armin Firouzi; Mahmood Moosazadeh; Seyyed Hossein Hosseini Karnami; Zahra karimian; Fatemeh Seyri (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Sexual knowledge and attitudes play a crucial role in marital relationships. Studies on Iranian youth preparing for marriage have indicated limited sexual knowledge and prevalent misconceptions about sexuality. This study aimed to evaluate the impact of multidimensional sexual education and counseling on the sexual knowledge and attitudes of couples preparing for marriage. Materials and methods: This randomized controlled trial included 43 couples in both the intervention and control groups, all of whom had attended marriage classes at the Kashan City Health Center. Participants were randomly assigned to the two groups. Sexual knowledge and attitudes were assessed using Snell's Sexual Awareness Questionnaire and Ozgoli's Sexual Attitude Questionnaire, respectively. Four educational-counseling sessions were conducted via Sky Room, an online platform. Online questionnaires were completed before the intervention, immediately after, and three months post-intervention. Data analysis was performed using SPSS version 25. Results: The sexual knowledge scores for women and men before the intervention were 50.53 ± 6.09 and 51.44 ± 5.17 in the intervention group, and 61.09 ± 5.75 and 61.86 ± 6.01 in the control group. Immediately after the intervention, the scores were 87.60 ± 7.65 and 54.46 ± 5.14 for the intervention group, and 95.81 ± 7.57 and 63.37 ± 5.63 for the control group. Three months later, the scores were 78.11 ± 7.20 and 65.06 ± 4.77 for the intervention group, and 88.86 ± 8.01 and 70.86 ± 4.87 for the control group. The sexual attitude scores for women and men before the intervention were 25.20 ± 4.95 and 23.95 ± 3.39 for the intervention group, and 22.53 ± 4.07 and 22.30 ± 3.94 for the control group. Immediately after the intervention, scores were 30.55 ± 4.32 and 27.93 ± 2.79 for the intervention group, and 25.86 ± 3.37 and 21.86 ± 3.37 for the control group. Three months later, the scores were 30.34 ± 4.23 and 27.90 ± 2.71 for the intervention group, and 26.01 ± 3.27 and 22.25 ± 3.28 for the control group. The mean scores for sexual knowledge and attitudes showed a significant increase immediately after and three months following the intervention, compared to the control group, for both women and men (P < 0.001). Conclusion: The multidimensional educational-counseling program is an effective method for improving couples’ sexual knowledge and attitudes. It is recommended that this approach be incorporated into pre-marital counseling programs for couples preparing for marriage.